Faces in the dark: interactive effects of darkness and anxiety on the memory for threatening faces - Nakashima, Satoshi F.; Morimoto, Yuko; Takano, Yuji; Yoshikawa, Sakiko; Hugenberg, Kurt (Frontiers in Psychology, 2014)
In the current research, we extend past work on the effects of ambient darkness and threat to the domain of memory for expressive faces. In one study, we examined the effects of ambient darkness and individual differences in state anxiety on memory of unfamiliar expressive faces. Here, participants were seated in either a dark or light room and encoded a set of unfamiliar faces with angry, happy, and neutral facial expressions. A subsequent recognition task revealed an interactive effect of ambient darkness, anxiety, and target expression. Highly anxious participants in ambient darkness had worse memory for angry faces than did low-anxiety participants. On the other hand, the recognition performance for happy faces was affected neither by the darkness nor state anxiety. The results suggest not only that ambient darkness has its strongest effect on anxious perceivers, but also that person x situation effects should be considered in face recognition research.